The Trithorax protein Ash1L promotes myoblast fusion by activating Cdon expression - Ilaria Castiglioni (Nature Portfolio, 2018)
Myoblast fusion in skeletal muscle is a complex process but how this is regulated is unclear. Here, the authors identify Ash1L, a histone methyltransferase, as modulating myoblast fusion via activation of the myogenesis gene Cdon, and observe decreased Ash1L expression in Duchenne muscular dystrophy.